2017
DOI: 10.4209/aaqr.2016.10.0466
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antimicrobial Activity on Non-Conducting and Conducting Air Filters by Using Air Ions and Grapefruit Seed Extract

Abstract: The application of grapefruit seed extract (GSE) and air ions to filters was investigated with the goal of collecting indoor bioaerosols. GSE exhibits antimicrobial activity because it contains flavonoids such as naringin. Air ions are usually generated by electric ionizers and can inactivate bacteria, viruses, and fungi. In this study, GSE particles were coated onto three different filters: polypropylene (PP), activated carbon fiber (ACF), and metal foam (MF). Ions were supplied to the filter surface using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The produced MOF filters demonstrated excellent performance for PM removal under a wide range of working temperatures from 80 to 300°C. The PM removal efficiency of the ZIF-8@plastic mesh (Figures 11(c Meanwhile, the accumulation of microorganisms in the filter also blocks the filter, leading to reduced ventilation volume and deterioration of the filter [160][161][162]. Thus, it is highly desirable to develop air filters with antimicrobial properties, especially when the filters are used for respiratory protection, such as masks, and for indoor air purification.…”
Section: Electret Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…The produced MOF filters demonstrated excellent performance for PM removal under a wide range of working temperatures from 80 to 300°C. The PM removal efficiency of the ZIF-8@plastic mesh (Figures 11(c Meanwhile, the accumulation of microorganisms in the filter also blocks the filter, leading to reduced ventilation volume and deterioration of the filter [160][161][162]. Thus, it is highly desirable to develop air filters with antimicrobial properties, especially when the filters are used for respiratory protection, such as masks, and for indoor air purification.…”
Section: Electret Membranesmentioning
confidence: 99%
“…Though air filters discussed above show excellent capture efficiency for particular matters (PM), microorganisms (or bioaerosols), such as bacteria, viruses, and fungi in the air, adhere to the filter surface, remain viable, and may reproduce within the filter media, which pose a risk of second airborne contamination. Meanwhile, the accumulation of microorganisms in the filter also blocks the filter, leading to reduced ventilation volume and deterioration of the filter [ 160 162 ]. Thus, it is highly desirable to develop air filters with antimicrobial properties, especially when the filters are used for respiratory protection, such as masks, and for indoor air purification.…”
Section: Engineering Of Multifunctional Masks and Mask Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[262] In general, the antimicrobial performance of herbal extracts is commonly attributed to the flavonoids that they may contain, which can kill microorganisms by disrupting cell membrane function and inhibiting deoxyribonucleic acid (DNA) cyclase. [263,264] Besides licorice extracts, it was also found that some herbal plants with antimicrobial properties, such as sage, garlic, oregano, fennel, etc., can reduce some symptoms of infectious individuals and may prevent the transmission of COVID-19. [265][266][267][268][269] In addition, Sim et al developed an Activated Carbon Fiber (ACF) filter incorporated with Sophora Flavescens, and they reported that the ACF filter showed an antibacterial efficiency >90%.…”
Section: Bio-based Substances or Herbal Extractsmentioning
confidence: 99%
“…Hence, they can become localized in the filter and their population can grow, which decreases filter quality and impacts air purification. Further, viable organisms present in the filter cause secondary infection after disposal, which is a major cause of the spread of disease. Various antimicrobial agents, such as graphene, MOFs, metal oxide, and NPs, can be incorporated in the filter to remove microbial load and efficiently filter air …”
Section: Involvement Of Nanotechnology To Improve the Quality Of Face...mentioning
confidence: 99%